A Perspective on Emerging Therapeutic Interventions for COVID-19 - Torequl Islam, Muhammad; Nasiruddin, Md.; Khan, Ishaq N.; Mishra, Siddhartha Kumar; Kudrat-E-Zahan, Md.; Alam Riaz, Thoufiqul; Ali, Eunus S.; Rahman, M. Safiur; Mubarak, Mohammad S.; Martorell, Miquel; Cho, William C.; Calina, Daniela; et al. (Frontiers in Public Health, 2020)
Coronaviruses (CoVs) are enveloped positive-sense RNA viruses with an unusually large RNA genome, and a unique replication strategy, and are characterized by club-like spikes that project from their surface. An outbreak of a novel coronavirus 2019 (nCoV-2019) infection has posed significant threat to international health and economies around the world. This review provides an introduction of the novel coronavirus with discussion on its replication and pathogenicity, current prevention and treatment strategies, and future directions for preventing the breakout. With the lack of approved and established treatment options for this virus, to find alternative methods to control the spread of disease is an urgent need. A survey is being presented for some possible coronavirus-infection treatment options as well as some other RNA-virus infections. Observations represent the plausible options for general treatments, coronavirus-specific treatments, and antiviral treatments might be useful in fighting coronavirus disease 2019 (SARS-COV-2). In addition, this study also examines some of the management strategies which can be applied to the evolving situation of this virus breakout. Taken all together, the study suggests that if the infection is a type of pandemic breakout, all potential interventions might be implemented to control the emerging SARS-COV-2. This review signifies the demographic emergence of zoonotic virus to humans and raises the concern for further explorations and outreach of research information towards SARS-COV-2 management and therapy.